AB0602 Anti-TNF Treatment for Refractory Vascular Involvement of BehÇEt's Syndrome: A Report of 16 Patients. (10th June 2014) - Hamuryudan, V.; Seyahi, E.; Melikoglu, M.; Ugurlu, S.; Hatemi, G.; Yurdakul, S.; Yazici, H.
Abstract : Background: The optimal management of vascular involvement and especially pulmonary artery involvement (PAI) in patients with Behçet's syndrome (BS) is still a challenge. Objectives: To evaluate the efficacy and safety of anti-TNF therapy in BS patients with major vascular involvement. Methods: We retrospectively reviewed the charts of 17 BS patients (16 men) with vascular involvement who had been treated with anti-TNF agents because of an inadequate response to traditional immunosuppressives (cyclophosphamide or azathioprine combined with corticosteroids). We excluded 1 male patient who developed pulmonary arterial aneurysms (PAA) with a fatal outcome while being under treatment with infliximab for neurological disease for 2 years. Results: Ten of the 16 patients had PAI, 5 had major vein involvement and 1 had renal artery aneurysm. PAI was in the form of PAA in 2 patients, pulmonary artery thrombosis (PAT) in 6 patients and the combination of PAA with PAT in 2 patients. Six patients (5 having PAI) also had intracardiac thrombi formation. All patients were using immunosuppressives at the time of initiation of anti TNF therapy (for 11±7 SD months in patients with PAI and 50±51 SD months in patients with other vascular involvement). The initial anti TNF agent was infliximab (5mg/kg) in 15 patients and adalimumab (40 mg eow) in 1 patient who had combined PAA and PAT. Additionally, all patients used varying dosages of corticosteroids and 10 used immunosuppressives (azathioprine =7). At the time of survey closure (December 2013) all patients were being followed, with all but 3 being still on anti TNF therapy. The treatment was effective in controlling the symptoms in all patients and none of the patients showed an exacerbation or new development of vascular involvement under anti TNF therapy (for a mean of 16±13.6 SD months for PAI patients and 19.5±14.9 SD months for patients with other vascular involvement). Anti TNF treatment (all infliximab) had been discontinued in 5 patients (4 with PAI). In 3 patients (2 with PAI) this was due to stable disease after a mean of 22.7±12 SD months treatment. One of these patients with PAA is on maintenance treatment with azathioprine and is symptom free 8 months after withdrawal. The second patient with PAT experienced hemoptysis due to development of a new PAT 3 years after withdrawal. He responded to re-institution of infliximab, which was switched to adalimumab after the second infusion because of an allergic reaction. The third patient with extensive venous involvement developed new venous thrombosis and secondary amyloidosis 1 year after withdrawal. His clinical status improved with re-institution of infliximab but he was also switched to adalimumab again because of the development of an allergic reaction. In 2 remaining patients with PAI infliximab was withdrawn because of serious infections (lung tuberculosis and fungal infection). The patient developing tuberculosis is still receiving anti-tuberculous treatment with no immunosuppressives and the second patient with fungal infection was subsequently prescribed interferon alpha. Conclusions: Our uncontrolled experience suggests that anti TNF therapy effectively suppresses signs and symptoms of major vascular involvement of BS. The development of serious infections under this therapy and relapses after withdrawal underline the importance of close follow-up. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1805